2000
DOI: 10.1002/(sici)1522-2594(200001)43:1<45::aid-mrm6>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine administration decreases functional connectivity in human primary visual and motor cortex as detected by functional MRI

Abstract: Functional magnetic resonance imaging (fMRI) was conducted to observe the effects of cocaine administration on the physiological fluctuations of fMRI signal in two brain regions. Seven long‐term cocaine users with an average age of 32 years and 8 years of cocaine use history were recruited for the study. A T2*‐weighted fast echo‐planar imaging (EPI) pulse sequence was employed at 1.5 T to acquire three sets of brain images for each subject under three conditions (at rest, after saline injection, and after coca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
95
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(99 citation statements)
references
References 25 publications
4
95
0
Order By: Relevance
“…Nevertheless, Gollub et al (8) noted that functional activation by visual stimulation, as measured by BOLD contrast, did not change significantly after cocaine administration, although blood flow was decreased by 14% due to cerebrovascular constriction. In a previous work we also demonstrated that acute cocaine administration alters functional synchrony in the visual and motor cortex regions, as observed by fMRI using spontaneous low-frequency component analysis (9).…”
supporting
confidence: 52%
“…Nevertheless, Gollub et al (8) noted that functional activation by visual stimulation, as measured by BOLD contrast, did not change significantly after cocaine administration, although blood flow was decreased by 14% due to cerebrovascular constriction. In a previous work we also demonstrated that acute cocaine administration alters functional synchrony in the visual and motor cortex regions, as observed by fMRI using spontaneous low-frequency component analysis (9).…”
supporting
confidence: 52%
“…Thus, these fluctuations agree with the concept of functional connectivity: a descriptive measure of spatio-temporal correlations between spatially distinct regions of cerebral cortex [Friston et al, 1993]. Several recent studies have shown decreased low-frequency correlations for patients in pathological states (such as multiple sclerosis [Lowe et al, 2002] or cocaine use [Li et al, 2000]). Accordingly, low-frequency functional connectivity may be important as a potential indicator of regular neuronal activity within the brain.…”
Section: Introductionsupporting
confidence: 84%
“…While the functional connectivity of these circuits in cocainedependent individuals has been measured in a resting state Hu et al, 2015;Li et al, 2000;Tomasi et al, 2010), the goal of this study was to investigate the functional connectivity in these circuits when they were engaged by an external source. The primary results demonstrate that (1) ventral striatal areas responsible for limbic arousal are not as responsive to the same level of medial prefrontal stimulation in cocaine users as controls (consistent with opponent process theory), (2) dorsal striatal areas typically implicated in cognitive control and habit formation have similar response profiles in cocaine users and controls, and (3) the reciprocal relationship between DLPFC stimulation and Brodmann 10 (MPFC) attenuation observed in controls is disrupted in cocaine users.…”
Section: Discussionmentioning
confidence: 91%